2014
DOI: 10.1159/000363072
|View full text |Cite
|
Sign up to set email alerts
|

Central Fat Accumulation Associated with Metabolic Risks beyond Total Fat in Normal BMI Chinese Adults

Abstract: Objective: To investigate the association of central fat with metabolic risks in normal BMI Chinese people. Methods: Normal BMI subjects (18.5 ≤ BMI < 24, n = 520) aged 18-82 years were included. Blood pressure, triglycerides, high-density lipoprotein cholesterol and fasting plasma glucose were collected as metabolic risk factors. Dual-energy X-ray absorptiometry was used to measure total and central fat. Central fat was indicated as percent trunk fat (%TF) and android/gynoid fat ratio. Multiple adjusted regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…Moreover, the proportion at high risk was the highest in non-obese individuals in the lowest LF/TF ratio tertile, highlighting the importance of the LF/TF ratio in non-obese patients. These findings support previous studies suggesting the importance of the fat distribution effect to risk of CVD in people with normal BMI [39], and implying that regional fat can distinguish high CVD risk patients in a non-obese group [40, 41]. In non-obese group with diabetes, the correlation was not significant in our result might suggest the overwhelmed impact of diabetes on CVD.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the proportion at high risk was the highest in non-obese individuals in the lowest LF/TF ratio tertile, highlighting the importance of the LF/TF ratio in non-obese patients. These findings support previous studies suggesting the importance of the fat distribution effect to risk of CVD in people with normal BMI [39], and implying that regional fat can distinguish high CVD risk patients in a non-obese group [40, 41]. In non-obese group with diabetes, the correlation was not significant in our result might suggest the overwhelmed impact of diabetes on CVD.…”
Section: Discussionsupporting
confidence: 90%
“…This somewhat deviates from a previous study that showed a negative correlation between slow HRR and HbA1c in obese patients with Type 2 diabetes [18]. However, in our study, we did not measure abdominal obesity or visceral fat, which might have influenced HRR among those with normal BMI if they had abdominal obesity despite a normal BMI [19]. Studies showed that the central fat in particular, abdominal visceral obesity was associated with impaired sympathetic nervous system function more than peripheral fat [20].…”
Section: Discussioncontrasting
confidence: 91%
“…DXA (GE Lunar Prodigy, WI, USA with software version 11.40.004) was implemented to measure body fat distribution as previously described [ 21 ]. The bone mineral density, fat mass, and lean soft tissue mass of the whole body and specific regions of interest (limb, trunk, android region, and gynoid region) were measured.…”
Section: Methodsmentioning
confidence: 99%